IMPLEMENTASI METODE PROTOTYPE PADA SISTEM INFORMASI DIGITAL ANGKRINGAN BERBASIS WEB DI KECAMATAN MAYONG - Indra Kurniawan; Roma Dhoni; Deva Arya Saputra; Fakhri Rahmat Wahyudin; Ahmad Mubais (Universitas Islam Nahdlatul Ulama Jepara, 2023)
Information systems are designed to provide information that interacts systematically and regularly, to make it easier for information seekers to obtain the information they want. Branding can be used to introduce the company's brand and build a positive image and company reputation so that it is always good in the eyes of consumers. Research on Digital Information Systems for Angkringan in Mayong District was designed with the aim of adding and displaying a floor plan of the locations of the angkringan in the Mayong sub-district along with their menus and also the conditions of the surrounding scope so that it can make it easier for people to choose and find the location of the angkringan as desired. The prototype method is used in making this application with the stages: (1) Communication, (2) Quick Plan, Modeling and Quick Design, (3) Construction of Prototype, (4) Development, Delivery and Feedback. This method is proven to facilitate the creation of an angkringan digital information system. The prototype method can be used well in developing web-based angkringan applications in Mayong District. The angkringan digital information system in Mayong District can display angkringan lists, angkringan addresses, angkringan products, whatsapp links and angkringan google maps.